The objective of this experiment was to screen 16 soybean genotypes tolerance to double stresses of Al toxicity and drought stress. A pot experiment was conducted at Cikabayan Experimental Station of Bogor Agricultural University from January to Maret 2004. Soybean plants were grown in Gajrug ultisol soil with pH 3.9 and Al saturated 26.61 me/100 g of soil. Al toxicity and drought tolerance were measured from the root length of seedling grown in 75% Al saturation and 40% field capacity compar - Chairani Hanum; Wahju Q. Mugnisjah; Sudirman Yahya; Didy Sopandie; Komaruddin Idris; Asmarlaili Sahar (Forum Pasca Sarjana, 2009)
The objective of this experiment was to screen 16 soybean genotypes tolerance to double stresses of Al toxicity and drought stress.  A pot experiment was conducted at Cikabayan Experimental Station of Bogor Agricultural University from January to Maret 2004.  Soybean plants were grown in Gajrug ultisol soil with pH 3.9 and Al saturated 26.61 me/100 g of soil.  Al toxicity and drought tolerance were measured from the root length of seedling grown in 75% Al saturation and 40% field capacity compared to 25% Al saturation and 80% field capacity.  The decrease of root length much lower at 75% Al saturation and 40% field capacity. Result of the study showed that soybean of Moket, B.3799, Malabar, Wilis, Sindoro, and Slamet were tolerant while Dieng, Sinyonya, B.3780, Sicinang, B.3578, Ceneng, Epyek, MLG 3072, and Tidar were susceptible to Al toxicity and drought stress. Key words: soybean, Al toxicity, drought stress, selection